TRIGO PARA A PRODUÇÃO DE SILAGEM (TRITICUM AESTIVUM CV. ENERGIA I E ENERGIX) SUBMETIDO A DOSES CRESCENTES DE ADUBAÇÃO MINERAL - Bertolini, Agatha; Dias, Chérllyn Marcel Alves; Sordi, André; Battiston, Joziane (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2020)
Wheat is a winter poaceae, of extreme importance for human food. Currently, alternatives are sought in the production of food for animals, in space in periods where there is a lower availability of food. Thus wheat for silage production is a viable and efficient alternative for producers, especially in the Southern Region. The study was carried out in the municipality of São José do Cedro, SC, evaluating the cultivars TBio Energia I® and TBio Energix®, and the treatments were: without the use of mineral fertilization in cover; 50% of the recommended mineral fertilization dose; 100% of the recommended mineral fertilization dose and 150% of the recommended fertilization dose. In this study, the production of MV, DM, percentage of N, P and K, export of nutrients N, P and K, rate of enjoyment of nutrients N, P and K, % of CP and evaluation of SPAD index in 30, 40 and 50 days after cultivation were evaluated. The two cultivars studied presented an excellent productive potecial for the region. Both showed a similar behavior pattern in their production. The cultivar TBio Energia I® in the treatment 100% and 150% of the recommended dose, presented the best results for MV,MS, % of N, P and K, and % of CP. The cultivar TBio Energix® only for the variable MS, did not present the best results.